Construction Waste Material Management and Logistic System - Othuman Mydin, Md Azree; Khor, Jie Cheng (Eftimie Murgu University of Resita, 2014)
Construction is one of the industries that produces significant amount of waste. Construction site produces waste as a result of construction work. In the context of direct waste, it is a mixture of surplus materials arising from any kind of construction works, be it construction, site clearance, excavation, renovation or refurbishment. Construction waste consumes a large amount of natural resources and hence a strategic management is significant to reduce or manage construction waste. There are studies showing that waste represents a relatively high percentage of production costs. Previous researcher defined waste as the loss of any kind of resources produced by activities which generate direct or indirect costs and do not add any value to the final product from the point of view of client. The society’s concern has gone from the perspective of efficiency to the impact to the environment. It is undeniable that the waste generated has caused an impact to the environment. However, building waste can hardly be recycled as it may be highly contaminated in the process of production or assembly. Building materials and inventory on site will contribute to waste generation if not handled properly and systematically. This paper will discuss some important elements of construction waste and management such as waste material management, construction logistic system and generation of construction waste.